Analysing short-track speed skating performance factors - Claudel, J.; Clément, J. (Sports Biomechanics, 2025)
Short-track speed skating is an incredibly precise sport, where even the smallest technical or physiological adjustment can profoundly impact performance, underscoring the importance of its study for achieving success. This study aims to identify short-track speed skating performance factors and quantify their impacts on athletes` performances. Twenty-nine short-track speed skaters (16 males and 13 females), with two different skill levels (National Elite and Junior Elite athletes), participated in this study. Movella IMU Link suits and Python scripts were employed to record and analyse one on-ice high-speed trial per athlete, focusing on lower body kinematics. From an initial pool of 535 tested factors, Pearson`s product moment correlations and stepwise multiple linear regression identified seven significantly associated with lap time, with notable differences between sex and skill levels. Results revealed that inter-foot spacing and pelvic height, which are actionable by athletes, could each contribute to a gain of up to 0.51 seconds per lap if improved by 10 cm. For an average lap on a 500 m race, this means a 5.2%-time improvement. This research enhances the understanding of short-track speed skating performances by identifying factors that can improve lap times, offering practical implications for coaching strategies and athlete training programs.